ANALYSIS OF THE OBJECTIVE SIDE OF CRIMINAL OFFENSES PROVIDED FOR IN THE DISPOSITIONS OF ART. 180 OF THE CRIMINAL CODE OF UKRAINE - Kovtun, Oleksii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: a comprehensive analysis of the objective aspect of criminal offenses, the legal compositions of which are stipulated in the provisions of Article 180 of the Criminal Code of Ukraine, considering the principles of criminal law theory. Research methods: deduction, formal-legal, logical-legal, cognitive-analytical, comparative-legal analysis, hermeneutic, and others Results: the proposed resolution of certain significant contentious issues regarding the objective elements of crimes defined in the provisions of Article 180 "Obstruction of Religious Worship" of the Criminal Code of Ukraine, specifically, the definition of "religious worship" as the circumstances of the commission of a criminal offense, the interpretation of the term "coercion" in light of the term "extortion" and the use of the terminological phrase "form of committing a socially dangerous act". Discussion: the study is dedicated to analyzing contentious issues concerning the objective aspect of the legal compositions of crimes stipulated in the provisions of Article 180 "Obstruction of the Performance of a Religious Rite" of the Criminal Code of Ukraine. Specifically, it addresses the interpretation of the terms "obstruction", "coercion", "religious rite" and the identification of specific types of socially dangerous acts as forms of committing a crime. Since criminal law theory defines the objective aspect of a criminal offense as one of the elements of the composition of a criminal offense, an analysis of domestic legal scientific literature allowed us to formulate the definition of the objective aspect of the composition of a criminal offense as a set of features prescribed by the law on criminal liability. These features characterize the observable and examinable external manifestation of the criminal offense and include the socially dangerous act (action or inaction), socially dangerous (criminal) consequences, and the causal link between the act and the consequences, as well as the place, time, context, method, tools, and means of committing the crime.